Cryptocurrencies and financial education: An educational approach to responsible adoption - Salcedo Tito, Rosa Angélica (2024)
The technical complexity and specialized terminology of cryptocurrencies have been persistent obstacles to general understanding. Compounding this problem, the lack of financial education has further limited the accessibility of these concepts. This study was dedicated to addressing such challenges by exploring the intersection between cryptocurrencies, financial education, and responsible adoption. The main objective was to provide a clear and accessible view of these concepts, thus promoting understanding and facilitating informed decision making. Their contribution lies in the responsible adoption of cryptocurrencies through practical tools and an accessible educational approach. The research used a descriptive documentary approach, using methods of collection and analysis of primary and secondary sources. The search focused on scientific articles indexed in recognized databases, such as Scopus, Scielo, Redalyc, Google Scholar, among others. Analysis tools were used to examine the connection between cryptocurrencies and financial education. The results underlined the crucial importance of financial education in the detailed understanding of cryptocurrencies. It was evident that effective educational approaches are essential to address technical and conceptual aspects, highlighting the critical need for specific educational programs for responsible adoption and safe practices in the emerging financial sphere of cryptocurrencies. It was concluded that financial education is essential to adopt cryptocurrencies responsibly. The importance of educational programs that address technical aspects and risks was highlighted. The need for policies that drive informed decisions was highlighted, thus strengthening responsible and sustainable participation in this growing financial field.